2021
DOI: 10.7554/elife.64714
|View full text |Cite
|
Sign up to set email alerts
|

Rapid recycling of glutamate transporters on the astroglial surface

Abstract: Glutamate uptake by astroglial transporters confines excitatory transmission to the synaptic cleft. The efficiency of this mechanism depends on the transporter dynamics in the astrocyte membrane, which remains poorly understood. Here, we visualise the main glial glutamate transporter GLT1 by generating its pH-sensitive fluorescent analogue, GLT1-SEP. FRAP-based imaging shows that 70-75% of GLT1-SEP dwell on the surface of rat brain astroglia, recycling with a lifetime of ~22 s. Genetic deletion of the C-termin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 66 publications
2
30
0
Order By: Relevance
“…Furthermore, we calculated the surface density of astrocytic membrane in stratum radiatum of the mouse hippocampus using 3D axial STEM tomography reconstructions (see below). Based on this analysis, the estimated astroglial surface density is 3.15 μm 2 /μm 3 . With these assumptions, we were able to estimate the average number of GLAST and GLT-1 molecules/μm 2 on the membrane surface of hippocampal astrocytes in tissue samples from different age groups: from 2 weeks to 21 month old mice.…”
Section: Ethics Statementmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, we calculated the surface density of astrocytic membrane in stratum radiatum of the mouse hippocampus using 3D axial STEM tomography reconstructions (see below). Based on this analysis, the estimated astroglial surface density is 3.15 μm 2 /μm 3 . With these assumptions, we were able to estimate the average number of GLAST and GLT-1 molecules/μm 2 on the membrane surface of hippocampal astrocytes in tissue samples from different age groups: from 2 weeks to 21 month old mice.…”
Section: Ethics Statementmentioning
confidence: 95%
“…Glutamate removal from the extracellular space relies on passive diffusion and active transport, a phenomenon mediated by transporter molecules abundantly expressed in the plasma membrane of astrocytes [1][2][3]. In the rat hippocampus, * 57% of excitatory synapses are contacted by astrocytic membranes, which surround * 43% of the synaptic perimeter [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent publication, we used fluorescence recovery after photobleaching in organotypic rat hippocampal sections to demonstrate that 70–75% of GLT-1 molecules dwell on the astrocyte surface, recycling with a lifetime of ∼22 s [ 117 ]. Using SMLM in cultured rat hippocampal cultures, we showed that GLT-1 surface expression and clustering behaviour relies on its C-terminus and its deletion accelerates GLT1 membrane turnover ( Figure 2 A) [ 117 ].…”
Section: Super-resolution Imaging Of Tripartite Synapsesmentioning
confidence: 99%
“… ( A ) Wide-field fluorescent images highlighting GLT-1 (green) and PSD95 (magenta) in mixed hippocampal astroglia-neuron cultures (top row). SMLM images showing individual labelled GLT-1 (green) and PSD95 (magenta) localisations (middle row depicting yellow squares in top row; bottom row depicting red squares in the middle row); modified from [ 117 ] with permission. ( B ) ExM image of dendrite and spines of a CA1 pyramidal neuron (green, YFP) and surrounding GLT-1 (red) labelling; with regions of ‘colocalisation’ highlighted in blue; modified from [ 119 ] with permission.…”
Section: Super-resolution Imaging Of Tripartite Synapsesmentioning
confidence: 99%